Needs Analysis of The Development of Digital Teaching Materials Using Moocs to Improve Students' Concept Understanding of Temperature and Heat Materials at SMAN of Bengkulu City - Triwahyuni Agustina (CV. Media Inti Teknologi, 2023)
This study aims to describe the feasibility of digital teaching materials using MOOCs to increase students' conceptual understanding of temperature and heat materials and to obtain good perceptions from students. This research was conducted at SMAN 2 Bengkulu City, SMAN 5 Bengkulu City, and SMAN 10 Bengkulu City. This research was conducted in October 2022 with a research sample of 3 physics teachers and 100 class XI MIPA students. The instruments used in this study were observation, interviews, and questionnaires. Data analysis and data collection techniques used were observation, interviews, and questionnaires. This research is research and development (R&D) with the 4D model which in this study is only the Define stage. The results of the data obtained from the responses of 72.41% of students with the agree category and 71.42% of teacher responses with the category of strongly agreeing is needed development of digital teaching materials using MOOCs to improve students' understanding of the concept of temperature and heat.